Interest representation in the European Union. 3rd ed. - Greenwood, Justin (Basingstoke, 2011)
"The fully revised third edition of this highly-acclaimed book provides an authoritative and comprehensive assessment of the role of organized interests in the EU. Showing that interest representation is a key aspect of the European project, it examines the significance of interests for everyday policy-making, for European integration, and for the democratic legitimacy of the EU. Accessibly written and thoroughly updated, the new edition contains additional material on the regulation of lobbying and the European Transparency Register."